Antibiofilm activity of mushroom extracts against Staphylococcus aureus - Čuvalová , Anna; Strapáč , Imrich; Handrová, Livia; Kmeť , Vladimir (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2018)
Mushrooms are a renowned source of products with an array of bioactivities, from antibacterial to antiviral, cytotoxic, antifeeding, antifungal or antioxidant and might be a valuable resource in the search of new bioactive extracts to inhibit biofilm production. We demonstrate the effect of five mushroom water extracts Macrolepiota procera, Pleurotus ostreatus, Auricularia auricula-judae, Armillaria mellea and Laetiporus sulphurous on biofilm formation of four Staphylococcus aureus strains isolated from ixodid ticks (Acari) and ewe´s milk. The PCR was used for detection of virulence genes (hla, isdA, B, bbp, sirB, fnbpA, sdrE, agr II). The ability of biofilm formation and anti-biofilm activity of mushrooms extracts was assessed in a quantitative crystal violet assay. The biofilm formation of S. aureus strains was significantly reduced by all mushrooms extracts (p < 0.001). We showed that more significant anti-biofilm effect of the extracts was of Staphylococcus aureus isolated from ixodid ticks in comparison to Staphylococcus aureus isolated from ewe´s milk. In the present study, A. mellea, P. ostreatus, L. sulphurous, A. auricula-judae and M. procera extracts inhibited biofilm formation by 70.87%, 67.00%, 64.14%, 62.77% and 47.71%, respectively. The results suggest that compounds in mushrooms extracts might be useful to control and handle detrimental infections caused by animal and human pathogens.